2004
DOI: 10.1074/jbc.m400894200
|View full text |Cite
|
Sign up to set email alerts
|

Sir Antagonist 1 (San1) Is a Ubiquitin Ligase

Abstract: Mutations in Sir Antagonist 1 (SAN1) suppress defects in SIR4 and SPT16 in Saccharomyces cerevisiae. San1 contains a RING domain, suggesting that it functions by targeting mutant sir4 and spt16 proteins for degradation by a ubiquitin-mediated pathway. Consistent with this idea, mutant sir4 and spt16 proteins are unstable in SAN1 cells but are stabilized in san1⌬ cells. We demonstrate that San1 possesses ubiquitin-protein isopeptide ligase activity in vitro, and the ubiquitin-protein isopeptide ligase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 68 publications
2
44
0
Order By: Relevance
“…Cells were grown at 37°C and induced for 1.5 h at an optical density at 600 nm of 0.6 to 0.7 with 0.3 mM IPTG (isopropyl-␤-D-thiogalactopyranoside). Cell lysates were made by sonication in a buffer containing 50 mM Tris-Cl, pH 8.0, and 1 mM EDTA, as described previously (11). Lysate (10 ml) was incubated for 1 h at 4°C with 1 ml prewashed GST-Sepharose beads in the presence of 1% Triton X-100 and protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were grown at 37°C and induced for 1.5 h at an optical density at 600 nm of 0.6 to 0.7 with 0.3 mM IPTG (isopropyl-␤-D-thiogalactopyranoside). Cell lysates were made by sonication in a buffer containing 50 mM Tris-Cl, pH 8.0, and 1 mM EDTA, as described previously (11). Lysate (10 ml) was incubated for 1 h at 4°C with 1 ml prewashed GST-Sepharose beads in the presence of 1% Triton X-100 and protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether the RING domain is important for the in vivo function of Rkr1, we mutated the first cysteine of the RING domain, changing it to an alanine (Rkr1-C1508A). Similar substitutions have been shown to disrupt the functions of other RING domain-containing proteins (11,80 RKR1 were transformed with plasmids expressing wild-type and C1508A forms of Rkr1. Growth assays showed that strains expressing wild-type Rkr1 grow on media lacking inositol, while strains expressing Rkr1-C1508A grow as poorly as rkr1⌬ strains ( Fig.…”
Section: Rkr1 Contains a Conserved Functionally Important Ring Domainmentioning
confidence: 96%
See 1 more Smart Citation
“…The lack of activity of the autophagy-lysosome system in the nucleus (9) suggests that nuclear PQC depends entirely on the UPS. Supporting this hypothesis, studies demonstrated that the San1 E3 ligase, which shows specificity for nuclear aberrant proteins, plays a pivotal role in nuclear PQC in the budding yeast Saccharomyces cerevisiae (10,11). Furthermore, recent studies in mammalian cells and primary neurons suggest that the UHRF-2 E3 ligase is an essential molecule for nuclear polyglutamine degradation as a component of the nuclear PQC machinery (12).…”
mentioning
confidence: 96%
“…Nuclear PQC in the budding yeast Saccharomyces cerevisiae is controlled by the San1 ubiquitin ligase (29,37). San1 contains highly disordered regions that identify misfolded substrates by binding to exposed hydrophobic stretches on the substrate (38 -43).…”
mentioning
confidence: 99%